Evidence from phylogenetic and genome fingerprinting analyses suggests rapidly changing variation in Halorubrum and Haloarcula populations - Ram Mohan, Nikhil; Fullmer, Matthew S.; Makkay, Andrea M.; Wheeler, Ryan; Ventosa, Antonio; Naor, Adit; Gogarten, J. Peter; Papke, R. Thane (Frontiers in Microbiology, 2014)
Halobacteria require high NaCl concentrations for growth and are the dominant inhabitants of hypersaline environments above 15% NaCl. They are well-documented to be highly recombinogenic, both in frequency and in the range of exchange partners. In this study, we examine the genetic and genomic variation of cultured, naturally co-occurring environmental populations of Halobacteria. Sequence data from multiple loci (~2500 bp) identified many closely and more distantly related strains belonging to the genera Halorubrum and Haloarcula. Genome fingerprinting using a random priming PCR amplification method to analyze these isolates revealed diverse banding patterns across each of the genera and surprisingly even for isolates that are identical at the nucleotide level for five protein coding sequenced loci. This variance in genome structure even between identical multilocus sequence analysis (MLSA) haplotypes indicates that accumulation of genomic variation is rapid: faster than the rate of third codon substitutions.